Sentiment Analysis to Improve the Quality of Public Transportation Services "Suroboyo Bus" - Kumalasari, Anisa Tri; Handayani, Wiwik (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Public transportation is a very important tool in improving and developing the economy of an area. The role of public transportation is very important in supporting mobility or community movement. Increased community mobility at the same time can have an impact on congestion. Congestion still occurs a lot and is a fairly complex problem in big cities, one of which is in Surabaya. The government is trying to reduce congestion in Surabaya by creating a safe and comfortable service innovation in the world of transportation, one of which is the Suroboyo Bus. This research is descriptive quantitative research. the method used is the random forest method. The tool used for data analysis is Rapidminer 10.3.1. The results of data analysis found several things that need to be improved by Suroboyo Bus to improve the quality of its services, namely those related to the words bus stops, routes, hours, applications, buses, etc. These words need to be considered to improve the quality of Suroboyo Bus services.